2007
DOI: 10.1097/01.nnr.0000299853.52429.62
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Basel Extent of Rationing of Nursing Care Instrument

Abstract: Initial evidence of the validity and reliability of the BERNCA instrument was provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
428
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(448 citation statements)
references
References 18 publications
13
428
1
6
Order By: Relevance
“…Most studies measured missed care with nurse or patient surveys that have been widely used in the missed care literature, namely survey from the International Hospital Outcomes Consortium [IHOC]/RN4CAST (Sermeus et al., 2011); MISSCARE (Kalisch, 2006) and the Basel Extent of Rationing of Nursing Care: BERNCA (Schubert, Glass, Clarke, Schaffert‐Witvliet, & De Geest, 2007). Three studies were secondary analyses of the large RN4CAST study conducted across 15 European countries (Ausserhofer et al., 2013; Ball, Murrells, Rafferty, Morrow, & Griffiths, 2014; Bruyneel et al., 2015), where authors analysed and reported data from individual countries.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies measured missed care with nurse or patient surveys that have been widely used in the missed care literature, namely survey from the International Hospital Outcomes Consortium [IHOC]/RN4CAST (Sermeus et al., 2011); MISSCARE (Kalisch, 2006) and the Basel Extent of Rationing of Nursing Care: BERNCA (Schubert, Glass, Clarke, Schaffert‐Witvliet, & De Geest, 2007). Three studies were secondary analyses of the large RN4CAST study conducted across 15 European countries (Ausserhofer et al., 2013; Ball, Murrells, Rafferty, Morrow, & Griffiths, 2014; Bruyneel et al., 2015), where authors analysed and reported data from individual countries.…”
Section: Resultsmentioning
confidence: 99%
“…In resource-constrained work environments, activities requiring interaction with patients can fall by the wayside (Aiken et al, 2001;Kalisch, Landstrom, & Williams, 2009;Lucero, Lake, & Aiken, 2009;Schubert, Glass, Clarke, Schaffert-Witvliet, & De Geest, 2007).…”
mentioning
confidence: 99%
“…Missed nursing care has been linked to negative patient outcomes (Schubert, Glass, Scaffert-Wiltvliet & De Geest., 2009) and attributed to a variety of causes from the work environment, to patient care demands and staffing issues (Kalisch, Doumit, Lee & Zein 2013;Papastavrou, Panayiota & Georgios, 2013;Aitken, Clarke & Sloane, 2002;Needleman, Buerhaus, Mattke, Srewart & Zelevinsky, 2002). Current research suggests that when a nurse's work load increases, there is less time to care for individual patients (Schubert, Glass, Schaffert-Witvliet & De Geest 2008).…”
Section: Introductionmentioning
confidence: 99%